2019
DOI: 10.3390/jof5030055
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Aspergillosis by Aspergillus flavus: Epidemiology, Diagnosis, Antifungal Resistance, and Management

Abstract: Aspergillus flavus is the second most common etiological agent of invasive aspergillosis (IA) after A. fumigatus. However, most literature describes IA in relation to A. fumigatus or together with other Aspergillus species. Certain differences exist in IA caused by A. flavus and A. fumigatus and studies on A. flavus infections are increasing. Hence, we performed a comprehensive updated review on IA due to A. flavus. A. flavus is the cause of a broad spectrum of human diseases predominantly in Asia, the Middle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
158
2
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(173 citation statements)
references
References 134 publications
6
158
2
7
Order By: Relevance
“…Analysis of macroscopic and microscopic characteristics is the most commonly used approach to diagnose for the aetiological agents of invasive and non‐invasive aspergillosis . Accurate species‐level identification of the pathogen responsible for invasive aspergillosis has become a major challenge in the management of the disease because very closely related species in the Aspergillus genus, including A flavus show different patterns of susceptibility to the main antifungal agents . Huang et al reported a poor accuracy rate of a culture‐based method for the species‐level discrimination among Aspergillus isolates, especially those belonging to cryptic and novel species.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of macroscopic and microscopic characteristics is the most commonly used approach to diagnose for the aetiological agents of invasive and non‐invasive aspergillosis . Accurate species‐level identification of the pathogen responsible for invasive aspergillosis has become a major challenge in the management of the disease because very closely related species in the Aspergillus genus, including A flavus show different patterns of susceptibility to the main antifungal agents . Huang et al reported a poor accuracy rate of a culture‐based method for the species‐level discrimination among Aspergillus isolates, especially those belonging to cryptic and novel species.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, invasive aspergillosis involving severe infections of the lungs are primarily caused by A. fumigatus and associated with a mortality rate of < 90% in undiagnosed or late-diagnosed cases [47,61,62]. A. flavus, besides being the second most prevalent causative agent of invasive aspergillosis after A. fumigatus, also infects several crops and contributes substantially to aflatoxin-related deaths [63]. Other medically important fungi, causing deep-seated infections of visceral organs, such as the lungs, include Blastomyces dermatitidis, Paracoccidioides brasiliensis, Histoplasma capsulatum [64,65].…”
Section: Sumoylation In Human Pathogenic Fungimentioning
confidence: 99%
“…The most common etiological agent of invasive aspergillosis with a high morality is A. fumigatus, responsible for the majority (up to 90%) of cases in humans [1,12,[15][16][17][18][19]. It is followed by A. flavus, which causes up to 10% of cases of…”
Section: Etiology Of Invasive Aspergillosismentioning
confidence: 99%